Perlindungan Hukum Bagi Talent Dalam Bisnis Jasa Pacar Sewaan Yang Tergabung Dengan Agensi - Riska Anggraeni, Riska Anggraeni; Subekti, Subekti; Astutik, Sri; Marwiyah, Siti (Judge : Jurnal Hukum, 2025)
The phenomenon of the rental partner service business in major cities of Indonesia has created complex legal dynamics, particularly concerning the legal protection of talents who are part of agencies. This practice is generally carried out informally without written agreements, making talents vulnerable to exploitation, breach of contract, and even harassment. This study aims to analyze the legal relationship between talents, agencies, and clients in the rental partner service business and to examine the forms of legal protection available to talents from the perspective of the Indonesian Civil Code (KUHPerdata) and the Job Creation Law. The research applies an empirical legal method with statutory, conceptual, and sociological approaches. The findings reveal that, although this legal relationship can be categorized as a service agreement, the absence of written contracts and specific regulations results in a lack of legal certainty and adequate protection for talents. Therefore, more specific legal regulations and the implementation of formal work contracts are necessary to ensure the rights of talents in performing their profession safely and with dignity.